Health-Care Facilities accessibility Analysis Using GIS: A case Study of Uyo Municipal South –Eastern Nigeria - Ike, Felix; Esther, Nweke (European Journal of Applied Sciences, 2022)
As the urban area grows and expands, efficient services such as housing, education, transportation, infrastructure, and healthcare are required. Accessibility to health care facilities is an important vital component of human well-being and the long-term survival of urban life. Spatial disparities occur from the concentration of health facilities in one location. This study used GIS techniques and locally produced data to assess the level of accessibility to health care services in Uyo Urban, Akwa Ibom State, Nigeria. The obtained index from Nearest Neighbour Analysis is roughly 0.74, showing a clustered pattern. The Alpha of the connectedness estimate is roughly 0.5, indicating an average connected network. The Beta Index of 1.9 indicates that Uyo has a high level of connectedness. Furthermore, the Gamma index of 0.6, which equals 60%, demonstrates that the study region is reasonably connected. This indicates that all portions of the study region have a moderate potential for interaction. Seven communities were unable to generate the quickest path to healthcare facilities based on the origin-destination and service areas. Only 14% of the municipalities are within walking distance of the nearest health care services. We propose that the healthcare delivery system, specifically its distribution and accessibility, be reinforced as soon as possible to improve people's health. We believe that the use of GIS as a decision-support tool should be expanded in Uyo L.G.A.'s health policy.